Perspectives of Threat Modeling of a Secure Cloud Picture Archiving and Communication System - Awokola, J. A.; Emuoyibofarhe, O. N.; Omotosho, A.; Emuoyibofarhe, J. O.; Mebawondu, J. O. (Engineering, Technology & Applied Science Research, 2019)
The Picture Archiving and Communication System (PACS) used in electronic health, is computationally enhanced by the migration into the cloud, which reduces the cost of storage space and equipment. However, cloud-PACS technology is susceptible to threats and vulnerabilities. This paper implements a threat modeling approach on a cloud-PACS framework, using Microsoft Threat Modelling Tools. Security requirements and mitigation strategies were formulated for the implementation of the framework, in order to improve cloud PACS security.